2021
DOI: 10.3390/healthcare9081056
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Bone Mineral Density Measured by HR-pQCT in Patients with Psoriasis or Psoriatic Arthritis: A Systematic Review and Meta-Analysis with Trial Sequential Analysis

Abstract: Bone health in psoriasis and psoriatic arthritis has been emphasized in recent years. Novel imaging modalities allow investigations into volumetric bone mineral density (vBMD) and bone microstructure in psoriatic patients. However, literature regarding vBMD measured by high-resolution peripheral quantitative computed tomography (HR-pQCT) is inconclusive. We conducted a systematic review and meta-analysis to evaluate vBMD in patients with psoriatic disease. We searched PubMed, EMBASE, Web of Science, and Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In the same study, patients with mild psoriasis were reported to have similar risk for VF, or even higher when patients with severe psoriasis were considered (mild psoriasis, 1.07, 1.05; 1.10, and severe psoriasis, HR 95% CI 1.26, 1.15; 1.39) [172]. Finally, in two recent meta-analyses, Chen et al showed that, while the DXA-assessed BMD seems not to be significantly reduced in PsA patients compared to controls [173], when a more sophisticated imaging technique such as HR-pQCT is adopted, PsA show a lower average volumetric BMD (total, trabecular, and cortical) [174]. Furthermore, the increased OR for fracture was confirmed: OR 95% CI 1.09, 1.06; 1.12 [173].…”
Section: Systemic Bone Loss (Osteoporosis) In Psamentioning
confidence: 99%
“…In the same study, patients with mild psoriasis were reported to have similar risk for VF, or even higher when patients with severe psoriasis were considered (mild psoriasis, 1.07, 1.05; 1.10, and severe psoriasis, HR 95% CI 1.26, 1.15; 1.39) [172]. Finally, in two recent meta-analyses, Chen et al showed that, while the DXA-assessed BMD seems not to be significantly reduced in PsA patients compared to controls [173], when a more sophisticated imaging technique such as HR-pQCT is adopted, PsA show a lower average volumetric BMD (total, trabecular, and cortical) [174]. Furthermore, the increased OR for fracture was confirmed: OR 95% CI 1.09, 1.06; 1.12 [173].…”
Section: Systemic Bone Loss (Osteoporosis) In Psamentioning
confidence: 99%
“…However, this higher risk of fractures may not necessarily correlate with lower BMD or a higher risk of osteoporosis [96]. Another meta-analysis provided more in-depth evidence about the bone microstructure and bone strength in psoriatic disease [97]. Psoriatic patients had lower volumetric BMD than non-psoriatic controls.…”
Section: Bone Remodeling and Osteoporosis In Spondyloarthritismentioning
confidence: 99%